Al-Barq Dalam Tafsir Jami’ Al-Bayan Fi Ta’wil Al-Qur’an - Harahap, Huslaili Habiba (Jurnal El-Thawalib, 2022)
Most people think of a flash of lightning as an ordinary natural phonemenon as a sign of heavy rain. There are even people who think that lightning flashes are “food”, this is what happened to the people of Kampung Petir, dramaga District, Bogor Regency, West Java. For them, lightning stikes and deafening sounds have become their daily food. Burs caused by lighning strikes are only treated with red medicine like ordinary wounds. The former head of the lightning Village, Omang Rohmana, said that many house and trees there damaged by lightning. This was due to the high intensity of lightning there. The formulation of the problem in this study is how the interpretation of the word al-Barq according to Ibn Jarir Ath-Thabari in the interpretation of Jami’ Al-Baya Fi Ta’wil Al-Qur’an, and what is the wisdom of the existence of al-Barq according to Ibn Jarir Ath-Thabari. The type of reaserch used in this thesis is library research. The primary data source for research is the Tafsir Jami’ Al-Bayan Fi Ta’wil Al-Qur’an. The skundem data are in the form of books, journal, articles and word al-Barq becomes a key word in the Qur’an which will be seen in the thematic interpretation, by collecting verses that relate to the phenomenon of al-Barq. the results showed that the word “al-Barq” in the Qur’an contained five verses mentioned by Ibn Jarir Ath-Thabari interpreting the word “al-Barq” in two contexts. Hypocrites who prosess to belive in Allah. Second, in the contexts natural phonomena by interpreting the word “al-Barq” is a flash of light that can eliminate sight for anyone who sees it according to physics the light produced by lightning can beat the brightness of 10 million light bulbs with o power of 100watts in 3 months.